Interaction in the investigation of interference with public officials - Husieva, Vlada; Popov, Volodymyr (Archives of Criminology and Forensic Sciences, 2025)
Effective handling of tactical tasks during investigations into criminal offenses that interfere with governmental activities relies heavily on collaboration. Pre-investigation officers typically engage with operational units and state institutions. When cases involve issues beyond their expertise, they also coordinate with specialists and forensic experts. This article aims to identify the distinctive features and stages of this collaboration—used by investigators during the procedural exploration of interference offenses involving public officials—and to clarify its components and specific characteristics. The authors find that such interaction is marked by: at least two participating entities; a shared objective toward which the cooperation is directed; specific measures through which the cooperation manifests; coordination and harmonization in implementing these measures; legal frameworks shaped by the limits of official authority, the interaction partners, and their professional statuses.